Whatsa paintoonist? - Moriarty, Jerry 1938- (Fantagraphics Books, 2017)
"At the age of 76, the painter/cartoonist Jerry Moriarty moved from his studio loft in Manhattan, where he lived and worked for 49 years, to his childhood home in Binghamton, New York, where he spent his first 12 years. The artist uses this as an opportunity to interrogate his past via the act of painting as a mnemonic. He invents the teenaged Sally, based upon his sister Pat, with whom he talks and shares his paintings: "The painting becomes a time machine and I am there in the past visiting my Dad," he tells her."...
Keywords: Moriarty, Jerry -- Comic books, strips, etc; Moriarty, Jerry -- 1938-; Cartoonists -- New York (State) -- Binghamton -- Comic books, strips, etc; Wohnen; Comic; Autobiografie